Implementation of the PBL-STEM Model to Improve Students' Critical Thinking on Reaction Rate Material - Putri Fritami Ata; Agung Rahmadani; Farah Erika (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The application of PBL-STEM can encourage students to be independent in the learning process and emphasize the process of thinking critically and analytically to seek and find answers to a problem in question. This study used a true–experimental design with the Posttest Only Control Design type. The population in this study were all students of class XI SMA Kristen Sunodia Samarinda for the academic year 2022/2023 divided into 2 classes. This study aims to determine the effect of PBL-STEM in improving students' critical thinking skills. Sampling was done by cluster random sampling technique. The instruments used to measure students' critical thinking skills in chemistry were post-test questions, teacher and student observation sheets, and student response sheets (questionnaire). Data analysis was performed by t-test. The results of the t-test with Mann-Whitney obtained sig. (2-tailed) in both classes is 0.00 <0.05, it is concluded that Ha accepted the statement that there is an effect of the application of PBL-STEM on the critical thinking skills of class XI students at Christian Senior High School Sunodia Samarinda regarding reaction rates. The results of the teacher and student activity sheets in the experimental class were both in very good categories, as well as the student response to PBL-STEM learning, namely 77.2% of students agreed with the application of PBL-STEM in learning which can train students' critical thinking skills. This research discusses the analysis of how effective the influence of PBL and STEM integration is to improve critical thinking skills on reaction rate material so that this research can be used as a reference for applying PBL-STEM to other chemistry topics.